Kribiocosmus Kieffer (Diptera, Chironomidae) newly recorded in China, with description of a new species - Dong, Xue; Tang, Hongqu (Zootaxa, 2024)
A new species, Kribiocosmus yini Tang is described based on the male and female collected from South China. The new species is characteristic by the reduced inferior volsella and arrow-shaped anal point. A key to all the known species of the genus in the world is provided. This is the first record of Kribiocosmus Kieffer in China.